68 SEXUAL FUNCTION AFTER LIVER TRANSPLANTATION. (1st January 2006) - Allan, K.; Tombazzi, C.; Waters, B.; Riely, C. A.
Abstract : Background: Sexual dysfunction is a common complaint in patients with advanced liver disease. The impact of orthotopic liver transplantation on sexual function has not been well described. Aim: To determine the impact of liver transplantation on sexual function and identify the most frequent complaints and possible related factors. Methods: Telephone survey of patients who have undergone liver transplantation at the University of Tennessee, Memphis, from 1998 to 2004. A five-page questionnaire including questions related to biological function, sexual function, and specific sexual dysfunction was used. Specific sexual dysfunction included loss of libido, poor vaginal lubrication, dyspareunia, inability to reach orgasm, difficulty achieving erections, loss of early morning erections, and premature ejaculation. Results: Ninety-one of 183 living patients who underwent liver transplantation from 1/1998 to 4/2004 were interviewed. M/F 65/26, age mean 53.1, range 27-75, hep C: 47/non-hep C: 44. Overall 67/91 (83.5%) of patients reported complaints of sexual dysfunction after transplantation, 60/65 (92%) men and 16/26 (62%) female (p = .001). The main specific sexual dysfunction was inability to maintain erections in men (59%) and decreased vaginal lubrication in females (38%) (Table 1 ). Only 13/91 (14%) patients had improved sexual function after transplantation. No significant difference was found in this group in regard to age and etiology of the liver disease. Conclusions: Sexual dysfunction continues to have a high prevalence in patients after liver transplantation. Male gender is significantly associated with sexual dysfunction after liver transplantation.